Spatial communication systems across languages reflect universal action constraints - Kenny R. Coventry; Harmen B. Gudde; Holger Diessel; Jacqueline Collier; Pedro Guijarro-Fuentes; Mila Vulchanova; Valentin Vulchanov; Emanuela Todisco; Maria Reile; Merlijn Breunesse; Helen Plado; Juergen Bohnemeyer; et al. (United Kingdom, 2025)
The extent to which languages share properties reflecting the non-linguisticconstraints of the speakers who speak them is key to the debate regardingthe relationship between language and cognition. A critical case is spatialcommunication, where it has been argued that semantic universals shouldexist, if anywhere. Here, using an experimental paradigm able to separatevariation within a language from variation between languages, we testedthe use of s pa ti al d em on st ra tives—the most fundamental and frequentspatial terms across languages. In n = 874 speakers across 29 languages, weshow that speakers of all tested languages use spatial demonstratives as afunction of being able to reach or act on an object being referred to. In somelanguages, the position of the addressee is also relevant in selecting betweendemonstrative forms. Commonalities and differences across languages inspatial communication can be understood in terms of universal constraintson action shaping spatial language and cognition.